Rules - Lord, Cynthia (New York : Scholastic, 2008)
Frustrated at life with an autistic brother, twelve-year-old Catherine longs for a normal existence but her world is further complicated by a friendship with a young paraplegic.
Originally published: New York : Scholastic Press, 2006. With additional material.
"Includes after words bonus features"--Cover.
"Newbery honor book"--Cover.
"Apple signature"--P. [4] of cover.
Includes bibliographical references (p. [213-214]).
Keywords: Autism -- Fiction; Brothers and sisters -- Fiction; People with disabilities -- Fiction; Autism -- Fiction; Brothers and sisters -- Fiction; People with disabilities -- Fiction